The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1471-2431-12-142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of routine probiotic, Lactobacillus reuteri DSM 17938, use on rates of necrotizing enterocolitis in neonates with birthweight < 1000 grams: a sequential analysis

Abstract: BackgroundNecrotizing enterocolitis (NEC) is a disease in neonates, often resulting in death or serious medical or neurodevelopmental complications. The rate of NEC is highest in the smallest babies and many efforts have been tried to reduce the rate of NEC. In neonates born below 1500 grams, the rate of NEC has been significantly reduced with the use of various probiotics. This study examines the impact of routine use of a probiotic, Lactobacillus reuteri DSM 17938 (BioGaia®), on the rate of NEC in neonates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 21 publications
2
86
1
8
Order By: Relevance
“…[46][47][48] A report from a single site in the USA 46 compared the incidence of NEC in 79 babies (of birthweight ≤ 1000 g) born between 2009 and 2011 in whom L. reuteri was routinely administered and babies born in the previous 5 years; detailed feeding data were not reported and infants who died in the first week were excluded. A reduction in NEC Bell stage ≥ 2 from 15.1% to 2.5% was reported (p = 0.0475); there were baseline differences in the characteristics of the babies and between-year variation in NEC incidence.…”
Section: Observational Studies/historic Comparisonsmentioning
confidence: 99%
“…[46][47][48] A report from a single site in the USA 46 compared the incidence of NEC in 79 babies (of birthweight ≤ 1000 g) born between 2009 and 2011 in whom L. reuteri was routinely administered and babies born in the previous 5 years; detailed feeding data were not reported and infants who died in the first week were excluded. A reduction in NEC Bell stage ≥ 2 from 15.1% to 2.5% was reported (p = 0.0475); there were baseline differences in the characteristics of the babies and between-year variation in NEC incidence.…”
Section: Observational Studies/historic Comparisonsmentioning
confidence: 99%
“…6,7 Our recently published retrospective case series in neonates with birth weights of #1000 g documented an even larger reduction in NEC rates in this high-risk population. 8 NEC rates were reduced from 15.1% before routine Lactobacillus reuteri prophylaxis to 2.5% after routine prophylaxis with L. reuteri. Some authors caution against routine use of probiotics, citing concerns with product quality, confusion over the best strains of probiotic to select, and possible adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Data for this analysis include neonates administered L. reuteri DSM 17938 at a dose of 0.1 mL (approximately 550 million colony-forming units) daily, as in our original publication, 8 and an additional 43 neonates administered a dose of 0.2 mL daily (110 million colony-forming units). This was a retrospective chart review of 354 consecutive patients comparing the rates of NEC in neonates with birth weight # 1000 g, before introduction of L. reuteri (January 2004-June 2009), with routine use of L. reuteri in neonates # 1000 g birth weight (July 2009-June 2012), and was approved by the institutional review board and exempted from needing informed consent.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study that looked at a cohort of VLBW neonates with NEC (#1000 g) showed that infants administered Lactobacillus reuteri DSM 17938 had a lower incidence of NEC (64). In addition, multiple meta-analyses of prospective, randomized, placebo-controlled trials analyzed the impact of probiotics on reducing the prevalence of NEC in premature infants (65)(66)(67).…”
Section: Management Strategiesmentioning
confidence: 99%